Estimation and Comparison of Immunization Coverage under Different Sampling Methods for Health Surveys. (7th August 2014) - Nath, D. C.; Patowari, B.
Abstract : Immunization currently averts an estimated 2-3 million deaths every year in all age groups. Hepatitis B is a major public health problem worldwide. In this study, the estimates of hepatitis B vaccine coverage are compared among three sampling plans namely, 30 × 30 sampling and30 × 7 sampling method under cluster sampling and systematic random sampling schemes. The data has been taken from the survey "Comparison of Two Survey Methodologies to Estimate Total Vaccination Coverage" sponsored by Indian Council of Medical Research, New Delhi. It is observed that the estimations of proportions of this vaccination coverage are significantly not different at 5% level of probability. Both30 × 30 sampling and30 × 7 sampling will be preferred to systematic sampling in estimation of hepatitis B vaccine coverage for this study population because of quick estimation and lesser cost. The30 × 7 cluster sampling is the most recommended method for such immunization coverage especially in a developing country.